1995
DOI: 10.1073/pnas.92.15.6911
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae (TWAR) in coronary arteries of young adults (15-34 years old).

Abstract: Six of the 7 (86%) atheroma, 2 of the 11 (18%) with intimal thickening, and none of the 31 normal-appearing coronary samples were positive. Four were positive by PCR for cytomegalovirus, 2 from diseased arteries and 2 from normal arteries. Examination of the adjacent left coronary artery sample with a fat stain found abnormalities in 25 of the patients, but 19 still showed no evidence of atherosclerosis as a result of either examination. Thus, C. pneumoniae is found in coronary lesions in young adults with ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
2
9

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(164 citation statements)
references
References 23 publications
(28 reference statements)
7
146
2
9
Order By: Relevance
“…The presence of circulating immune complexes has been proposed as a marker for chronic C. pneumoniae infection in coronary artery disease [17], but it was not associated with asthma in this study. The presence of immune complexes containing chlamydial proteins points to free access ofchlamydial products into the circulation and could be a marker for, as an example, chlamydial infection of arteriosclerotic plaques [18]. IgA antibodies could better reflect chronic inflammation of mucous membranes in lung.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of circulating immune complexes has been proposed as a marker for chronic C. pneumoniae infection in coronary artery disease [17], but it was not associated with asthma in this study. The presence of immune complexes containing chlamydial proteins points to free access ofchlamydial products into the circulation and could be a marker for, as an example, chlamydial infection of arteriosclerotic plaques [18]. IgA antibodies could better reflect chronic inflammation of mucous membranes in lung.…”
Section: Resultsmentioning
confidence: 99%
“…Animal/experimental, pathological, and cross-sectional seroepidemiological studies conducted among middle-aged populations provide some support for the hypothesis that infections with herpes simplex virus type 1 (HSV-1), cytomegalovirus (CMV), and C pneumoniae are associated with the development of atherosclerosis and CHD. [5][6][7][8][9][10][11][12][13][14][15][16] However, recent reports from several prospective studies failed to demonstrate consistent associations between the presence of IgG antibodies to C pneumoniae, HSV-1, and CMV and incident MI. [17][18][19][20][21][22] Given both the high prevalence of IgG antibodies to these agents and the high incidence of cardiovascular disease among older adults, it is particularly important to determine whether serological evidence of prior infection with these agents, assessed late in life, is associated with incident MI and CHD death.…”
Section: T He Role Of Viruses and Other Infectious Agents Such Asmentioning
confidence: 99%
“…Campbell et al 9 showed the presence of the microorganism in 32% of the fragments of endarterectomy of coronary arteries in American patients. Kuo et al 8 , using the PCR technique, detected 14% positivity for Chlamydia pneumoniae in autopsy samples from atherosclerotic coronary arteries of American individuals, whose ages ranged from 15 to 34 years. Ong et al 16 , in the United Kingdom, showed the presence of Chlamydia pneumoniae in 44% of the fragments of aortic aneurysms and in 55% of the iliac arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The association of Chlamydia pneumoniae and coronary, carotid, and peripheral arterial disease has been described in several countries in diverse types of studies as follows: a) serum-epidemiological studies [2][3][4][5][6] ; b) anatomicopathological studies [7][8][9][10][11][12][13][14][15][16][17] ; and c) experimental studies [18][19][20][21][22] . Reports on cultivation of Chlamydia pneumoniae in fragments of arteries exist, showing the viability of the bacterium and its multiplication capacity in that type of environment 10,12 .…”
Section: Original Articlementioning
confidence: 99%